Virtual project management: introduction. (1st January 2012) - Leuthold, Christian; Huber, Charles; Plüss, Adrian
This article gives a short introduction into virtual project management and it shows that virtual teams and virtual project management have significant advantages like adding special expertise to a project team even though the expert is not in the same geographic area or drastically reduce of travel time. The major differences between virtual project management and classical project management can be found in the project communication and in project team management. The introduction includes also a short overview of the papers in this special issue.